DISTRIBUSI UNSUR UTAMA DAN UNSUR TANAH JARANG PADA PELAPUKAN BATUAN GRANITOID DI DAERAH PARMONANGAN, KABUPATEN TAPANULI UTARA: DISTRIBUTION OF MAJOR ELEMENTS AND RARE EARTH ELEMENTS IN THE WEATHERED GRANITOID ROCKS IN THE PARMONANGAN AREA, NORTH TAPANULI REGENCY - Ana Nurul Hidayati; Nurcahyo Indro Basuki; Sulaeman; Bayu Sayekti (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
The results of an investigation by PSDMBP in 2011 showed that the REE content in weathered granitoid at Parmonangan contained several elements with significant anomalies such as Ce (600 to 1400 ppm), La (400 to 1000 ppm), and Pr (600 to 1400 ppm). Therefore, further investigation needs to be carried out to determine the distribution of REE to the west of the previous investigation area. This study aims to determine the characteristics of the granitoid, weathering pattern, and profile of the REE content in the investigation area. The weathering of granitoid in the Parmonangan area comes from biotite granite and hornblende biotite granite. The geochemical characteristics of weathering indicate that Na2O, CaO, K2O, SiO2, P2O5, and MnO dissolve and are mobile during weathering, indicating a decrease in soil content compared to bedrock. Meanwhile, Al2O3, Fe2O3, TiO2, and LOI showed an increase in weathering results due to residual enrichment. The content of the weathered granitoid in the Parmonangan area shows the relative enrichment of LREE to HREE. The content of LREE is influenced by the distribution of La and Ce elements contained in monazite. The content of HREE is controlled by the distribution of element Y. Based on the Spearman correlation, titanite and apatite also affect the abundance of LREE. While the mineral-bearing HREE is zircon. The sample interval is in the REE leaching zone so that the concentration of REE obtained in the soil is lower than in the bedrock.